PENGARUH KEBIJAKAN DIVIDEN, PERTUMBUHAN PENJUALAN, UKURAN PERUSAHAAN, DAN GOOD CORPORATE GOVERNANCE TERHADAP HARGA SAHAM - Wiratama, Alfian Bagas; Kusumawati, Eny (Prosiding University Research Colloquium, 2021)
This study aims to analyze the effect of dividend policy, sales growth, company size, and good corporate governance on stock prices. Good corporate governance used is managerial ownership and independent board of commissioners. The population of this research is companies that are consistently included in the LQ-45 Index on the Indonesia Stock Exchange (IDX) during the 2015-2019 period. The number of samples taken was 115 data with 23 companies selected per year using purposive sampling technique. Data collection was carried out using documentary methods on secondary data. The analysis technique used is multiple linear regression analysis with the help of the SPSS 20 computer program. The results show that collectively, dividend policy, sales growth, company size, managerial ownership, and independent board of commissioners have a significant effect on stock prices. Partially, managerial ownership has a significant effect on stock prices, while dividend policy, sales growth, company size, and independent board of commissioners have no significant effect on stock prices.